2003
DOI: 10.1021/ac034437b
|View full text |Cite
|
Sign up to set email alerts
|

A Dry Process for Production of Microfluidic Devices Based on the Lamination of Laser-Printed Polyester Films

Abstract: A new microfabrication process based on a xerographic process is described. A laser printer is used to selectively deposit toner on a polyester film, which is subsequently laminated against another polyester film. The toner layer binds the two polyester films and allows the blank regions to become channels for microfluidics. These software-outlined channels are approximately 6 microm deep. Approximately twice this depth is obtained by laminating two printed films. The resulting devices were not significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 40 publications
1
94
0
6
Order By: Relevance
“…Among those devices designed for custom analytical and bioanalytical applications, microchip electrophoresis (ME) devices are some of the most important ones [6][7][8]. A variety of strategies have been employed in the production of devices for ME ranging from standard photolithography [9] to rapid prototyping [10][11][12] and assembly [13]. Although photolithographic techniques have been traditionally used to produce high-end devices using silica-based substrates, the process can be time-consuming and render chips that are (often) too expensive for most research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Among those devices designed for custom analytical and bioanalytical applications, microchip electrophoresis (ME) devices are some of the most important ones [6][7][8]. A variety of strategies have been employed in the production of devices for ME ranging from standard photolithography [9] to rapid prototyping [10][11][12] and assembly [13]. Although photolithographic techniques have been traditionally used to produce high-end devices using silica-based substrates, the process can be time-consuming and render chips that are (often) too expensive for most research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Tan e colaboradores 44 inicialmente propuseram o uso de máquinas fotocopiadoras para gerar moldes descartáveis, os quais foram então empregados para a rápida prototipagem de microestruturas em PDMS. Do Lago e colaboradores 45 propuseram um processo de impressão direta para a rápida produção de microdispositivos. Neste processo, os padrões de imagens são impressos sobre um filme de poliéster (transparência de retroprojeção) usando uma impressora laser para depositar seletivamente uma camada de toner, a qual define as dimensões dos canais microfluídicos.…”
Section: Processo De Impressão Diretaunclassified
“…13,14 Toner was firstly explored for microfabrication in 2001, when Tan et al 15 suggested the use of a photocopying machine to create a high-relief master for prototyping of microfluidic devices in poly(dimetilsyloxane) (PDMS) substrate. In 2003, do Lago et al 16 proposed the direct fabrication of microfluidic devices using a laser printer for the deposition of toner layers on polyester films followed by a thermal lamination for sealing of channels at low temperature. Since this pioneering report, laser printing technology (LPT) has been used to produce microfluidic toner-based analytical devices (µTADs) at very low cost.…”
Section: Introductionmentioning
confidence: 99%